2019
DOI: 10.3897/zoologia.36.e24191
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the factors determining rotifer assemblage in river-lake systems: the effects of seasonality and habitat

Abstract: Zooplankton exhibit several trends of variation in space and time, and these trends can be more evident in natural environments without anthropic perturbations. Examples of anthropic factors are climate change, eutrophication and construction of reservoirs. This study evaluated the influence of three factors – seasonality, type of environment and the presence of aquatic macrophytes – on various ecological attributes of rotifers in a river-lake system located in the Paraná River floodplain. Monthly samplings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(23 reference statements)
2
3
0
1
Order By: Relevance
“…The micro-communities in fresh water bodies constitute an extremely diverse assemblage of organisms represented by most of the invertebrate phyla, however, the dominant zooplankton includes rotifers, cladocerans, copepods and ostracods Kennie et al [11]. Planktonic organisms tend to be more abundant in lentic systems such as lakes compared to lotic systems such as rivers, most likely as a result of water flow, Serafim-Jr et al [28] revealed supporting the present results. Zooplankton communities' dynamics in the tropics has been attributed to a number of other factors such as the environmental characteristics of the water, predation, quality of edible algae and competition Hellawell [29]; Ovie and Adeniji [30].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The micro-communities in fresh water bodies constitute an extremely diverse assemblage of organisms represented by most of the invertebrate phyla, however, the dominant zooplankton includes rotifers, cladocerans, copepods and ostracods Kennie et al [11]. Planktonic organisms tend to be more abundant in lentic systems such as lakes compared to lotic systems such as rivers, most likely as a result of water flow, Serafim-Jr et al [28] revealed supporting the present results. Zooplankton communities' dynamics in the tropics has been attributed to a number of other factors such as the environmental characteristics of the water, predation, quality of edible algae and competition Hellawell [29]; Ovie and Adeniji [30].…”
Section: Discussionsupporting
confidence: 87%
“…Macrophytes provide a fundamental element in the trophic chain by offering a variety of microhabitats used as refuges against visual predators and as reproductive sites for different taxa Duggan et al [42] and Choi et al [43] and distinct species of macrophytes can promote the development of specific rotifer assemblages associated with the architecture of the habitat and the spatial distribution of these plants (Velho et al [44]; Lansac-Toha et al [45]; Colares et al [46]. Against these observations, Serafim-Jr et al [28] opined that the hydrological phases, months and the environment type were important factors in the ecological structure of rotifers. However, common freshwater rotifers such as Keratella sp reported by Egborge and Tawari [47]; Ekpo and Essien-Ibok [48] were not identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic macrophytes offer a set of potential advantages such as microhabitat diversity [6,11,13,14]; a variety of food resources (algae, bacteria, and detritus) [13][14][15]; refuge against predators [11,14,15]; and reproductive sites [16]. Particular characteristics of plants such as life form (floating, rooted, or submerged), morphological complexity and spatial structure, arrangement and orientation of leaves, stems, and roots [15,17], as well as age, density, and diversity of macrophytes [17,18], among others, create a heterogeneity of habitats and variable conditions that can influence the composition, richness, and density of the rotifers associated with them [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have registered complex and diverse associations of rotifers to structurally more complex macrophytes [15,17,18]. Studies carried out in ponds of flooded areas also have shown a higher diversity of rotifer taxa in the littoral zones compared to the pelagic zone [11,16,[19][20][21] Surprisingly, despite the high diversity of rotifers in littoral macrophyte habitats, there is still relatively little knowledge about the periphytic or planktonic rotifers associated with macrophyte patches. Therefore, the biodiversity of rotifers in these habitats must be considered important and must be used in the monitoring of aquatic ecosystems [12,22] and conservation/management plans [10].…”
Section: Introductionmentioning
confidence: 99%
“…A limitação de dispersão ambiental é considerada uma dos principais fatores que estruturam as comunidades aquáticas, e as espécies geralmente têm potenciais diferentes de dispersão (Beisner et al, 2006;De Bie et al, 2012 ). Além de a dispersão ser alterada, pode ocorrer a presença de espécies diferentes que não são provenientes da dispersão, mas sim carreadas da fauna litorânea (Serafim-Júnior et al, 2019).…”
unclassified